VIRAL MYOCARDITIS: CURRENT THERAPEUTIC APPROACHES AND CLINICAL EVIDENCE (Editora Impacto Científico, 2025)
This review article addresses myocarditis, an inflammatory disease of the heart muscle caused predominantly by viral infections. The introduction highlights the clinical heterogeneity of the condition, which ranges from mild cases to severe cases of cardiogenic shock and sudden death, and emphasizes the increase in its incidence following the SARS-CoV-2 pandemic. The pathophysiology is described as a phased process, beginning with direct viral injury and progressing to a host immune response that, when dysregulated, can cause chronic damage and dilated cardiomyopathy. The objective of the study is to synthesize the current evidence on therapeutic approaches, given that specific treatment is still limited and controversial. The methodology consisted of a narrative review of the literature, with a search of the PubMed database for relevant publications on the diagnosis and treatment of viral myocarditis, using MeSH descriptors such as "Viral Myocarditis" and "Treatment." The results and discussion categorize therapeutic approaches into three pillars. The first and main pillar is supportive treatment, focused on managing symptoms and cardiovascular complications, such as heart failure (with the use of beta-blockers and ACE inhibitors) and cardiogenic shock (with mechanical circulatory support, such as ECMO). The second pillar is antiviral therapy, which is not routinely used but has shown benefits in specific scenarios, such as the use of interferon-beta for enterovirus (BICC trial) and telbivudine for Parvovirus B19. The third pillar is immunomodulatory treatment (corticosteroids, IVIG), which remains controversial due to conflicting results in clinical trials. The article emphasizes the European Society of Cardiology's recommendation to perform an endomyocardial biopsy to rule out active viral infection before starting immunosuppression. Finally, new therapies under investigation, such as colchicine and IL-1 pathway inhibitors, are mentioned.